Gambaran Dukungan Keluarga Tentang Derajat Hipertensi Pada Lansia di Puskesmas Waplau Kabupaten Buru - Epi Dusra (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2023)
Factors that cause hypertension are age, gender, family history, genetics (risk factors that cannot be changed/controlled), smoking habits, obesity, lack of physical activity, stress, use of estrogen and one of the factors that can cause hypertension is salt consumption patterns. with excessive intake. The purpose of this study was to determine the description of family support with the incidence of hypertension in the elderly. The design used in this study is an analytic research design with a descriptive approach. The population in this study were 60 people. The sample in this study were 60 elderly people with hypertension. Data analysis using univariate analysis. And the data is presented in the form of tables and narratives. The results of the study showed that the family support of elderly respondents who was most commonly found in this study was in the negative category, totaling 46 people. In the degree of hypertension, the elderly respondents who were most commonly found in this study were in the category 1 hypertension category, namely 19 people. It was concluded that the most negative family support with the degree of hypertension found in this study was the category 1 hypertension.